PELATIHAN TARI KREASI SEBAGAI PENINGKATAN KOMPETENSI GURU MI/PAUD/RA RADEN FATAH - Emy Yunita Rahma Pratiwi; Ratih Asmarani; Evita Widiyati; Muhammad Nuruddin; Claudya Zahrani Susilo (LPPM UNIVERSITAS HASYIM ASY'ARI TEBUIRENG JOMBANG, 2020)
Abstract: This community service is one of the education services to the community,which is one of the programs in the field of KKNT of UNHASY Tebuireng Jombangstudents in Kedungbogo Village, Ngusikan District, Jombang Regency. One of those isconducting a dance training at Raden Fatah. The results of the study were: there is a lackof understanding of the concept and the importance of cultural arts education inclassroom learning in terms of students’ character development into humanisticcharacters through creativity, sense, and intention. The method used in implementing thiscommunity service is as follows: a) partner Situation Analysis, b) literature study, c)preparation of material to be presented as a problem solution, d) testing the results, e)revision products, f) the training implementation, and g) Regular mentoring.Based onthose problems, it can be concluded that a) there must be an improvement in skills andcompetence of teachers related to the teaching and learning process in the schoolsenvironments, b) this training (community service) is expected to make teachersunderstand the concept and the importance of cultural arts education c) there must be adevelopment of students’ character to become humanistic character through creativity,taste, and initiative, displaying an attitude of appreciation for cultural arts, displayingcreativity through cultural arts, and increase the participation of cultural arts events at thelocal, regional and global levels.Keywords: Dance, Competency, Professional, Teacher, Raden FatahAbstrak: Pengabdian ini merupakan salah satu pengabdian perguruan tinggi kepadamasyarakat, yaitu salah satu program di bidang pendidikan KKNT mahasiswa UNHASYTebuireng Jombang di Desa Kedungbogo Kecamatan Ngusikan Kabupaten Jombang,diantaranya melaksanakan Pelatihan Tari di Raden Fatah. Hasil analisis yang ditemukanadalah: Kurang adanya pemahaman konsep dan pentingnya pendidikan seni budayapada pembelajaran di kelas sehingga kurang dalam hal pengembangan karakter pesertadidik menjadi manusia yang humanistis melalui olah cipta, rasa, dan karsa. Metodepelaksanaan PKM adalah sebagai berikut: a) Analisis Situasi Mitra, b) Pengkajianpustaka c) Penyusunan materi sebagai solusi masalah, d) Uji coba, e) Revisi produk, f)Pelaksanaan pelatihan, dan g) Pendampingan berkala. Berdasarkan permasalahantersebut maka dapat disimpulkan bahwa perlu adanya a) peningkatan keterampilanmaupun kompetensi guru yang berkaitan dengan proses belajar mengajar di lingkunganSekolah Dasar/Madrasah Ibtidaiyah maupun PAUD/RA perlu ditingkatkan. b) adanyapelatihan dalam PKM ini diharapkan menjadikan guru memahami konsep dan pentingnyapendidikan seni budaya c) mengembangkan karakter peserta didik menjadi manusia yanghumanistis melalui olah cipta, rasa, dan karsa, menampilkan sikap apresiasi terhadap senibudaya, menampilkan kreativitas melalui seni budaya, dan meningkatkan peran serta senibudaya pada tingkat lokal, regional dan global.Kata Kunci: Tari, Kompetensi, Professional, Guru, Raden Fatah